Insert x + 3 instead of x into the equation of the function f(x):
f(x) = 3 - 6x²
f(x + 3) = 3 - 6(x + 3)²
use (a + b)² = a² + 2ab + b²
= 3 - 6(x² + 2(x)(3) + 3²) = 3 - 6(x² + 6x + 9)
use distributive property
= 3 + (-6)(x²) + (-6)(6x) + (-6)(9) = 3 - 6x² - 36x - 54
combine like terms
= -6x² - 36x - 51
<h3>Answer: f(x + 3) = -6x² - 36x - 51</h3>
Answer:
34.9^2
Step-by-step explanation:
Well if one side is 4 cm then the square is 16cm^2.
The area of a circle is pi r^2.
So the radius is 2.
we plug 2 in.
pi 4
12.6/2
6.3
6.3 * 3 = 18.9cm^2
18.9 + 16 = 34.9
We know that
<span>The nine radii of a regular Nonagon divides into 9 congruent isosceles triangles
</span>therefore
[the area of <span>a regular nonagon]=9*[area of isosceles triangle]
</span>[area of isosceles triangle]=b*h/2------> 15*20.6/2----> 154.5 cm²
so
[the area of a regular nonagon]=9*[154.5]------> 1390.5 cm²
the answer is
1390.5 cm²
All you need to do is 8 divided by 6. When you do so you get: 1.3 which could also be written as 1 3/8.
So each person gets 1 whole piece and 3/8 of another piece.